ANALYSIS OF TRANSLATION TECHNIQUE IN THE WEBTOON “SMILE BRUSH” BY WAROO - Salsabela Hasna Rosida; Dyah Nugrahani; Rahmawati Sukmaningrum (Melati Institute, 2023)
The purpose of this study were (1) to find out the translation techniques used in comics in the webtoon application entitled